2019
DOI: 10.1002/tcr.201800137
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Elucidation of Solid‐Electrolyte Interphase (SEI) Film Formation via Atomistic Reaction Simulations: Importance of Functional Groups of Electrolyte and Intact Additive Molecules

Abstract: Secondary batteries such as Li‐ion battery are expected to be utilized as not only ubiquitous electric power sources such as mobile phones but also large‐scale electricity storage devices. Therefore, it is urgent to develop the higher performance secondary batteries. Their lifetime and stability are found to be strongly dependent on the nature of passivation film called solid electrolyte interphase (SEI) film formed on the anode surface in the initial charge‐discharge cycle. However, since it is difficult to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Also, the RM method has shown great applicability in simulating the dynamic effect on SEI lm formation, such as the aggregation and the dissolution of the reduction reaction products. [59][60][61][62][63][64][65] In addition, the RM method has recently shown a high efficiency to treat the dynamic processes of catalytic polymerization reactions. 66,67 In fact, it can be applicable also to more complicated electrolyte systems such as polymer electrolytes or ionic liquids.…”
Section: Red Moon Methodology: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the RM method has shown great applicability in simulating the dynamic effect on SEI lm formation, such as the aggregation and the dissolution of the reduction reaction products. [59][60][61][62][63][64][65] In addition, the RM method has recently shown a high efficiency to treat the dynamic processes of catalytic polymerization reactions. 66,67 In fact, it can be applicable also to more complicated electrolyte systems such as polymer electrolytes or ionic liquids.…”
Section: Red Moon Methodology: An Overviewmentioning
confidence: 99%
“…More recently, we have theoretically observed that, on a similar structural basis, the cis-versus trans-conguration difference of butylene carbonate (BC) molecule brings about a similar stabilization difference during the microscopic SEI formation processes in LIBs. 65 In this way, the RM method has fruitfully bridged the gap between the computational investigations and experimental ones from the viewpoint of SEI lm formation. It can clarify the mystery of the conventional LIBs performance affected by the slight difference between EC and PC or BC, which is the presence or absence of a methyl group 62 or even just the difference between the cis-and trans-isomeric congurations of a unique molecule.…”
Section: Fec Additive Concentration Optimization For Advanced Nib Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the recently developed RM method [ 77 ] has greatly advanced the analysis of unexplored subjects that link elementary electrolyte reduction reactions to the morphological features of SEI layers. [ 62–69 ] In this regard, this review focuses on the aggregation process of electrolyte reduction products that ultimately leads to the formation of a stable SEI layer to ensure a longer lifetime and faster kinetics. Notably, the formation of SEI was found to proceed in a bottom‐up manner (Figures 4 and 8), which dominates the overall morphology of the SEI, such as the inorganic–organic bilayer structure in conventional electrolytes and the anion‐derived nature in concentrated electrolytes.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Although the compositional and morphological evolution during SEI growth has been studied by in situ experiments, [28,58,59] there is only a limited understanding of how the SEI structure is formed and what reactions dominate at each stage. Recently, theoretical studies using multiscale simulation methods, such as kinetic Monte Carlo (MC) [60,61] and Red Moon (RM) methods, [62][63][64][65][66][67][68][69] have emerged to bridge the gap between the conventional theoretical results (e.g., initial reduction reactions of electrolytes) and experimental ones (e.g., morphologies of the formed SEI layers). Elucidating these poorly understood intermediate steps will enable us to establish a new interphaseoriented electrolyte design that may realize next-generation batteries.…”
Section: Introductionmentioning
confidence: 99%